As propostas educacionais maranhenses no Império (1834-1889) - Cabral, Maria do Socorro Coelho (1982)
Following , the Additional Act of 1834, which placed the administration of primary and secondary public educa~ion in Brazil under the responsibility or local public instruction in the state of Maranhão 'authorities, undenV'ent ' a !ieries óf ·changes. Tml1ards the end- o,f the 1830' s and during the fourties and fifties, an effort was made by the State to exercise greater control over provincial instruction as well as to develop elementary education 1n the hopes of reachirig more of the publico It was during these years that the local administration began to stimulate the teaching of technical and agricultural issues and secondary education was recrgmized with ,the creation of the 'Liceu Maranhense'. However, during the last years of the empire the State began to show less interest in the development of formal education in Maranhão and the official accomplishments of this period, leveIs, were insignificant. By decreeing the free at, alI exercise of teaching in 1874, the State legally revealed its lack of interest in assuming the responsibility for public educ~t 'ion. The tendencies observed in Maranhão's instruction during the period from 1834-1889 have pub1ic been associated with the political and economic fàctors affecting the State during the same time period. In the early decades of the nineteenth-century, the politica1 situation in Mara nhão was char ac te ri ze d by the de te rminat ion o f th e 1 arge 1ándowners (a small fraction of the 'domÍt13nt c 1 a~.s in p owe r) , in guaranteeing order and in seeking an hegemouy. In the economic sphere, a trenA in favor of material reforms directed tow&ds the econimic recuperation of the ~arcanti1e economy cau be noted. However, during the 1ater decades analyzed, the po1itical situation of the landowners was strengthened, even though it continued to be threatened by a serious economic crisis. The social conditions. of Maranhio during the first decades of the century led to a greater interest in education on the part of the State, while during the later decades the general political and economic situation in Maranhio led to a decreasing interest in its public education.